The management of upper gastrointestinal bleeding in hemophilia patients by sclerotherapy - Nadir YÖNETÇİ,; Mustafa YILMAZ,; Ömer ÖZÜTEMİZ,; Fulya GÜNŞAR,; Ayhan DÖNMEZ,; Oktay TEKEŞİN,; Yücel BATUR,; Hanefi ÇAVUŞOĞLU, (Turkish Journal of Gastroenterology, 2019)
-